Issues and Challenges Confronting History Teachers in the Implementation of K-12 Curriculum in the Province of Sulu - Mohammad, Abdulla I. (Indonesian Community Empowerment Journal, 2021)
The K-12 program intended to produce graduates will be more prepared to enter the labor force. However, the problem concerning the implementation of the K-12 curriculum is the cost. Indeed, the benefits of K-12 implementation are correlated with the problems and challenges of its implementation for teachers and other stakeholders. This study aimed to determine the issues and challenges confronting history teachers in the implementation of the K-12 curriculum in the province of Sulu. This study used a survey research design. The data in this survey were sourced from the respondents, library works, and internet research. The participants of this survey study consisted of history teachers from the different public and private high schools in Sulu. Purposive sampling was employed in this study. It was purposive for the fact it uses history teachers in public and private high schools in some of the municipalities and provinces of Sulu for the school year 2018- 2019. The data from the respondents were obtained through the questionnaire. The result revealed that the history teachers strongly agreed on the issues and challenges that would serve as problem areas in the curriculum implementation namely, learning resources and needs, teacher’s competency, administrator’s competency and teaching, supervisor’s competency, monitoring, technical assistance, evaluation, and assessment. In conclusion, history teachers must improve their educational attainment and read more about techniques and strategies for history subjects in implementing the K-12 curriculum.